Pachychoroid Pigment Epitheliopathy and Choroidal Thickness Changes in Coeliac Disease. (13th February 2019) - Bolukbasi, Selim; Erden, Burak; Cakir, Akin; Bayat, Alper Halil; Elcioglu, Mustafa Nuri; Yurttaser Ocak, Serap; Gokden, Yasemin; Adas, Mine; Asik, Zekiye Nur
Abstract : Purpose . To evaluate choroidal thickness in patients with coeliac disease (CD) using spectral domain optical coherence tomography (SD-OCT) and to compare the results to normal eyes. Methods . Seventy patients with CD and 70 healthy controls were included in this prospective, comparative study. All participants underwent a complete ophthalmologic evaluation and SD-OCT. Subfoveal, nasal (nasal distance to fovea 500 μ m, 1000 μ m, and 1500 μ m), and temporal (temporal distance to fovea 500 μ m, 1000 μ m, and 1500 μ m) choroidal thickness measurements were performed using SD-OCT. Results . There were no significant differences in sex, ages, and axial lengths between the groups (p = 1.0, p = 0.601, p = 0.314, respectively). The mean choroidal thickness measurements at all predefined measurement point areas were higher in the coeliac group than in the healthy controls (p < 0.001 ). Of all patients with coeliac disease (70 eyes of 70 patients), 64 eyes (84.2%) had uncomplicated pachychoroid (UCP), one eye had pachychoroid pigment epitheliopathy (PPE), and five eyes in the UCP group had PPE in fellow eyes. Conclusion . It is probable that systemic inflammation in coeliac patients causes the enlargement of choroidal vessels and increasing choroidal thickness. PPE, which is believed to be the precursor of central serous chorioretinopathy, can be observed in coeliac patients.